SYNTHESIS, THERMAL REACTIVITY, AND ANTIOXIDANT STUDIES OF AMINOGUANIDINIUM SALTS OF ASPARTIC AND GLUTAMIC ACIDS - S, PARVEEN; D, MANIKANDAN; S, GOVINDARAJAN; PA, PERIASAMY (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: Our main scope and objectives are to prepare aminoguanidinium salts of amino acids and to characterize them using analytical, IR, and thermal studies, to study the mode of thermal decomposition of aminoguanidinium salts, and to characterize the antioxidants behavior of aminoguanidinium salts. Methods: Elemental analysis for C, H, and N was performed on a Vario ELIII elemental analyzer. The IR spectra were recorded on a JASCO-4100 spectrophotometer as KBr pellets in the range of 400–4000 cm-1. The simultaneous TG-DTA studies were under taken on a PerkinElmer SII thermal analyzer and the curves obtained in air using platinum cups as holders with ~ 3 mg of the samples at the heating rate of 10°C/min. The antioxidant capacities of different salts were estimated according to the literature procedure. Results: Aspartic acid forms bis-aminoguanidinium salt, whereas glutamic acid forms both mono- and bis-aminogunidinium salts. The IR spectral data of the aminogunidinium salts of aforesaid acids show N-N stretching frequencies in the region 1110–1202 cm-1 revealing the presence of aminoguanidinium moiety. Conclusion: The antioxidant properties of these salts were studied using ferric reducing antioxidant power and phosphomolybdenum assay. Results showed significant ferric reducing power which indicated the hydrogen-donating ability of the extract.